The molecular mechanisms of iron uptake and transport, isotopic fractionation patterns, and subcellular localization characteristics in rice - Yu, Anfeng; Li, Sixiang; Huang, Jianhao (Resources Data Journal, 2025)
Iron is an essential micronutrient for plant growth, development, and metabolism, playing a critical role in rice productivity, stress resistance, and grain nutritional quality. This study systematically investigated the molecular mechanisms of iron uptake and transport in rice, with a focus on the pivotal roles of iron transport proteins in root absorption, translocation to aboveground tissues, and phloem-mediated distribution to grains. The synergistic and antagonistic interactions between iron and other metal elements, such as zinc and cadmium, during absorption were also elucidated. Furthermore, by analyzing iron isotopic fractionation behavior in the soil-plant system, the study revealed the characteristics and ecological significance of isotopic fractionation during iron cycling, phase transformation, and chelation processes. Using high-resolution spectroscopic techniques, including X-ray fluorescence spectroscopy and synchrotron radiation X-ray absorption spectroscopy, the subcellular localization of iron was examined, uncovering its distribution across different subcellular components and its impact on rice iron metabolism. This integrative research provides a comprehensive understanding of the molecular mechanisms, isotopic fractionation patterns, and subcellular distribution of iron in rice, offering theoretical insights into the dynamic behavior of iron within the plant. The findings not only propose new strategies for improving rice iron use efficiency and grain nutritional value but also provide scientific evidence and technical references for addressing heavy metal contamination and enhancing soil environmental quality.